2021
DOI: 10.1038/s42003-021-02448-9
|View full text |Cite|
|
Sign up to set email alerts
|

Accumulation of formaldehyde causes motor deficits in an in vivo model of hindlimb unloading

Abstract: During duration spaceflight, or after their return to earth, astronauts have often suffered from gait instability and cerebellar ataxia. Here, we use a mouse model of hindlimb unloading (HU) to explore a mechanism of how reduced hindlimb burden may contribute to motor deficits. The results showed that these mice which have experienced HU for 2 weeks exhibit a rapid accumulation of formaldehyde in the gastrocnemius muscle and fastigial nucleus of cerebellum. The activation of semicarbazide-sensitive amine oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Administration with CoQ10 could also prevent the decline of ALDH2 expression (HH vs. HH + CoQ10, p = 0.0054) (Figure 3F) and activity (HH vs. HH + CoQ10, p < 0.0001) (Figure 3G) under hypobaric hypoxic conditions. These findings indicated that CoQ10 can prevent FA accumulation not only by combination with FA, 14,25 but also by preserving its normal metabolism.…”
Section: Nano-packed Coenzyme Q10 Prevented Formaldehyde Accumulation...mentioning
confidence: 80%
See 3 more Smart Citations
“…Administration with CoQ10 could also prevent the decline of ALDH2 expression (HH vs. HH + CoQ10, p = 0.0054) (Figure 3F) and activity (HH vs. HH + CoQ10, p < 0.0001) (Figure 3G) under hypobaric hypoxic conditions. These findings indicated that CoQ10 can prevent FA accumulation not only by combination with FA, 14,25 but also by preserving its normal metabolism.…”
Section: Nano-packed Coenzyme Q10 Prevented Formaldehyde Accumulation...mentioning
confidence: 80%
“…Excessive cerebral FA shows critically detrimental effect on the nervous system, while CoQ10 administration is useful in multiple neurological diseases 45 . It can directly combine with the FA molecule for elimination and function preservation 14,25 . It can also inhibit ALDH2 inactivation to promote clearance 46 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite its low level in the body, FA plays a crucial role in metabolic processes (Ye et al, 2013; Tang et al, 2013). Elevated levels of FA in the body can cause damage to critical systems, particularly the central nervous system, leading to difficulties in learning and memory impairment (Yao et al, 2021). Studies conducted on animals have shown that exposure to FA can result in significant deterioration in learning ability and memory, as well as morphological changes in rat hippocampal tissue (Li et al, 2020; Wei et al, 2022; Songur et al, 2003).…”
Section: Introductionmentioning
confidence: 99%